Rekomendasi Pelayanan Birokrasi di Masa Transisi Pandemi Covid-19 - Azis, Rifky Febrihanuddin; Husna, Nurul (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2022)
The outbreak of the Covid-19 pandemic in Indonesia has changed various dimensions of human life, including government bureaucratic services whose main task is to provide services to the public. Based on the background of the problem, the purpose of this study is to examine and provide recommendations on how bureaucratic services carry out their functions during the transition period of the Covid-19 pandemic. This study uses a qualitative approach with a systematic literature study. The data sources of this research are secondary in which the data are obtained from journals, books and articles. The results of the analysis show that bureaucratic management in the transition period of the Covid-19 pandemic faces 2 (two) challenges that must be solved, namely the internal dimension and the external dimension. The internal dimension is how to ensure that the apparatus can carry out their obligations in accordance with their respective duties and functions supported by predetermined outputs. The external dimension is how the bureaucracy is able to provide public services to the community with limited conditions that require the provision of public services to be based on health protocols. This condition is an opportunity for the bureaucracy to be able to formulate a Work From Anywhere (WFA) policy to carry out the work given based on performance-based optimal output.